1617g Association of insomnia and fatigue due to shift work in midlife and mobility limitations over 28 years of follow-up. (24th April 2018) - Prakash, KC; Neupane, Subas; Leino-Arjas, Päivi; Härmä, Mikko; Nygård, Clas-Håkan
Abstract : Objectives: We aimed to investigate the long-term association of insomnia and fatigue due to shift work (with and without night shifts) in midlife and mobility limitations (ML) among initially middle-aged subjects followed over 28 years. Methods: The Finnish Longitudinal Study on Ageing Municipal Employees (FLAME) was conducted by the Finnish Institute of Occupational Health from 1981 to 2009 among 6257 municipal workers. This study is based on the latest available response on ML questionnaires either from 1992 or 1997 or in 2009 (n=4704). International Classification of Functioning (ICF) was used to code the nine mobility tasks included in the ML. Insomnia and fatigue due to shift work were assessed using the yes/no questions in the baseline. The Incidence Rate Ratio (IRR) and 95% Confidence Interval (CI) for the association of insomnia and fatigue due to shift work and ML were assessed by using mixed Poisson regression. The results are presented separately for women and men in shift work with and without night shifts. Results: After adjusting for age, smoking, alcohol use, BMI, physical exercise and chronic diseases, women engaged in shift work without night shifts in midlife had on average a 24% (due to shift work insomnia) and a 16% (due to shift work fatigue) higher risk for a unit increase in ML in old age than those without shiftwork insomnia and fatigue. Likewise, men engaged in shift work with night shifts in midlife had on average a 61% (insomnia) and a 66% (fatigue) higher risk for a unit increase in ML in old age. Furthermore, women in shift work with night shifts and men in shift work without night shifts had on average a higher risk of ML, but the risk was attenuated and remained insignificant after adjustment. Conclusions: The findings of this prospective 28 year cohort study suggest that shift work related insomnia and fatigue in midlife have inverse effects on mobility functions in old age irrespective of gender and type of shift work, and indicates in the initiation of prevention of mobility decline in working life.